Performance comparison of two route optimisation schemes for AODV in MANETs. (2016) - Khan, Bilal; Bilgin, Zeki
In this study, we extend performance evaluation of two different 'route optimisation' schemes proposed in Bilgin and Khan (2010) and Bilgin et al. (2010), with new performance metrics like normalised energy consumption, packet delivery fraction, average end-to-end delay, and average connection lifetime. In addition, we provide performance comparison of this two schemes against each other with pure AODV as a reference. The compared schemes are implemented as extension of AODV in ns-2 packet level network simulator. The first scheme, called 1-hop shrink, periodically checks if there is any shortcut (i.e., direct connection) between two endpoints of each successive and overlapped triplet of nodes along active routes. On the other hand, the second scheme, called multi-hop shrink, periodically checks if there is a shortcut between any two nodes on a route by broadcasting a special packet starting from at the third node on active connections.